Hierarchy Analysis, Leading Commodities and Community Participation in Agropolitan Areas in Trenggalek Regency, East Java Province - Angga Pratama Putra; Budi Setiawan; Suhartini Suhartini (HABITAT, 2021)
The agropolitan area in Trenggalek Regency is one of the regional development programs that began in 2006.The objectives of this study are 1) Determining the hierarchical structure of growth and service centers in an agropolitan area, 2) Determining superior commodities that can be developed in an agropolitan area, 3) Knowing perceptions and levels of community participation as well as the factors that influence it in an effort to increase active community participation as the main actor in agropolitan area development. The research location was determined purposively. This study uses two types of data, namely primary data and secondary data. The analytical methods used in this research are 1) scalogram analysis, 2) Location Quotient / LQ analysis, 3) non-parametric chi-square statistical analysis. Based on the schalogram analysis of villages in the agropolitan area in Trenggalek Regency, it is obtained a hierarchy of regions in the agropolitan area in Trenggalek Regency, so that Tasikmadu, Pule, Jombok and Sumurup Villages are the centers of growth and service centers while the development areas of Karanggandu Village, Prigi, Watulimo, Sawahan, Watuagung, Sidomulyo, Tanggaran, and Dompyong are agropolitan areas. While other development areas, namely the Dukuh, Slawe, Gemaharjo, Pakel, Ngembel, Puyung, Joho, Kembangan, Pakel, Masaran, Sengon, Srabah, Surenlor and Botoputih development areas are hinterland areas. Based on the results of the LQ analysis, the agropolitan area in Trenggalek Regency has 34 (thirteen) commodities that have an LQ value of more than 1: leaves, potatoes, mustard greens, long beans, large chilies, bird's eye chilies, green beans and chayote, c) Fruit crop subsectors: avocado, star fruit, duku, durian, guava, water guava, orange siem, large orange, mangosteen, jackfruit, papaya, rambutan, salak, sapodilla and soursop, d) Sub-sector of plantation crops: Patchouli, sugarcane, cocoa, cloves, coffee, vanilla and cottonwood. The level of public perception towards agropolitan programs is relatively poor. The level of community participation in agropolitan programs is relatively low. The intrinsic factors that have a real influence on the level of participation are income and land area, while the extrinsic factors are socialization, assistance, openness of government, program suitability and benefits. Increasing community participation can be done by improving the factors that have a real influence.